[Heat modification of the mutational process and heat shock proteins.] - Tikhomirova, M.M.; Mazur, E.L.; Barabanova, L.V.; Mamon, L.A. (Genetika, 1993)
Heat shock protein synthesis and mutagenesis (X-chromosome losses induced by radiation and high temperature) were studied in different. Drosophila melanogaster strains. Two models (strain l(1)ts403 with the defect in heat shock protein synthesis and the heat-resistant T strain with a specific reaction to the extreme temperature differing from the wild type strains) were used. The correlation between heat shock protein synthesis and the effect of synergism in the action of radiation and heat shock was revealed. It was concluded that HSPs are one of the components in mutagenic processes.